Efeito de uma intervenção educativa com enfermeiros para a vigilância do crescimento e do desenvolvimento infantil na consulta de puericultura: um estudo misto - Vieira, Daniele de Souza (2022)
Introduction: The nursing consultation in childcare provides the follow-up of the child, has the potential to promote health, effective monitoring of child development and, when performed with is an important strategy to prevent injuries and hospitalizations due to preventable causes. Objective: To evaluate the effect of an educational intervention and to apprehend the perception of nurses of the Family Health Strategy regarding the change of knowledge and practices of growth and development surveillance in childcare consultation. Methodological approach: Mixed multiphase study of intervention, with a quantitative qualitative approach, from the perspective of the theory of educational learning of David Ausubel, conducted from december 2020 to march 2021, with nurses working in the Family Health Strategy of the Health District I of the municipality of João Pessoa – Paraíba. To evaluate before and after the educational activity, we used an instrument previously constructed and validated, and semi-structured interviews, interpreted under the technique of thematic analysis. In the statistical analysis, descriptive analysis and inferential analysis were performed, applying the proportion tests, Wilcoxon and Item response theory with the Rasch model. The research project was approved by the Ethics Committee, under n. 26615819.1.0000.5188. Results: The integration of quantitative and qualitative data allowed the construction and validation of the data collection instrument. The nurses hit more items of the instrument and there was a significant decrease in the difficulty index after the intervention. In addition, there was a positive impact after the educational intervention in the acquisition of new knowledge and practices during the nurses' childcare consultation. Conclusion: The educational intervention on growth and development surveillance in childcare consultation was effective to improve the knowledge and practice of nurses working in the Family Health Strategy. It is believed that promoting permanent education and discussions about child development surveillance among multiprofessional teams help improve care.